Determination of the influence of the experimental program of basic elements on the formation of the factor structure of the assimilation of sports acrobatics by young novice athletes - Tetiana Chernykh; Daria Okun; Olena Tarasevich; Yaroslav Kraynik (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to study the influence of the experimental program on the formation of the factor structure of mastering the basic elements of the technique of young acrobats 6-7 years old. Material and methods: the study involved young novice acrobats 6-7 years old school No4 in the amount of 19 people (10 guys and 9 girls). General and specific physical exercises and psychophysiological characteristics were used as tests. The factor analysis of the calculation was used, which was carried out by the statistical method developed and presented in the works of S. Spearman and G. Thompson. Results: the conducted factor analysis made it possible to determine a number of factors that determine the quality of mastering the basic elements of sports acrobatics techniques by young athletes of 6-7 years old. Conclusions: it was found that in the process of applying the experimental program, a redistribution of factors was carried out: 4 groups of factors were identified: psychophysiological, general preparatory, specially preparatory and others in basic exercises ("swallow", "bridge", "standing on the shoulder blades, "forward roll", "wheel") in the direction of performing special preparatory exercises.